Acute cardiovascular hospitalizations and illness severity before and during the COVID‐19 pandemic. Issue 5 (7th March 2021) - Rao, Vishal N.; Kelsey, Michelle D.; Kelsey, Anita M.; Russell, Stuart D.; Mentz, Robert J.; Patel, Manesh R.; Fudim, Marat
Abstract: Background: Cardiovascular disease (CVD) hospitalizations declined worldwide during the COVID‐19 pandemic. It is unclear how shelter‐in‐place orders affected acute CVD hospitalizations, illness severity, and outcomes. Hypothesis: COVID‐19 pandemic was associated with reduced acute CVD hospitalizations (heart failure [HF], acute coronary syndrome [ACS], and stroke [CVA]), and worse HF illness severity. Methods: We compared acute CVD hospitalizations at Duke University Health System before and after North Carolina's shelter‐in‐place order (January 1–March 29 vs. March 30–August 31), and used parallel comparison cohorts from 2019. We explored illness severity among admitted HF patients using ADHERE ("high risk": >2 points) and GWTG‐HF (">10%": >57 points) in‐hospital mortality risk scores, as well as echocardiography‐derived parameters. Results: Comparing hospitalizations during January 1–March 29 (N = 1618) vs. March 30–August 31 ( N  = 2501) in 2020, mean daily CVD hospitalizations decreased (18.2 vs. 16.1 per day, p  = .0036), with decreased length of stay (8.4 vs. 7.5 days, p  = .0081) and no change in in‐hospital mortality (4.7 vs. 5.3%, p  = .41). HF hospitalizations decreased (9.0 vs. 7.7 per day, p  = .0019), with higher ADHERE ("high risk": 2.5 vs. 4.5%; p  = .030), but unchanged GWTG‐HF (">10%": 5.3 vs. 4.6%; p  = .45), risk groups. Mean LVEF was lower (39.0 vs. 37.2%, p  = .034), with higher mean LV mass (262.4 vs. 276.6 g, p  = .014). Conclusions: CVD hospitalizations, HF illness severity, and echocardiography measures did not change between admission periods in 2019. Evaluating short‐term data, the COVID‐19 shelter‐in‐place order was associated with reductions in acute CVD hospitalizations, particularly HF, with no significant increase in in‐hospital mortality and only minor differences in HF illness severity.